(1228) Barge carrying system as a factor of improving transportation service of the developing countries نظام النقل النهري كعامل لتحسين خدمات النقل في البلدان النامية - Muller, Alexander M. (The Institute Of National Planning., 2018)
Growth in international trade among the different groups of countries, including the exchange between the industrial countries and the developing ones, has resulted in a contiual increase of maritime shipping.